A Review on Self Nano-Emulsifying Drug Delivery System - Shivangi Purohit,; Dr. Meenakshi Bharkatiya, (Asian Journal of Pharmaceutical Research and Development, 2025)
Self-nanoemulsifying drug delivery systems (SNEDDS) have gained traction as an effective solution for enhancing the solubility of hydrophobic medications. These systems aim to overcome challenges associated with the limited bioavailability of poorly soluble and highly permeable compounds. SNEDDS are composed of isotropic blends of oil, surfactants, solvents, and co-solvents. They have proven to be successful in improving the solubility and bioavailability of drugs that struggle with water solubility. Typically formulated as liquids, various techniques such as extrusion, melting, spray-drying, and freeze-drying have been developed to convert liquid SNEDDS into solid forms. SNEDDS not only demonstrate a notable increase in dissolution rate but also minimize interfacial tension. The continuous advancement of SNEDDS technology is poised to open up innovative applications in drug delivery, offering solutions to challenges associated with the distribution of poorly soluble drugs.